STUDY OF 7 BUILDING DEVELOPMENT PLANNING SPECIFICATION OF STEEL FRAMEWORK STRUCTURE (BASED ON SNI 1729 - 2015) (CASE STUDY: OFFICE BUILDING CONSTRUCTION PROJECT) - Tomi Admanegara; Koespiadi Koespiadi (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2019)
Steel is a material that is widely used in industrial development and buildings with functions as the main building frame. This plan aims to plan a building structure with 7 floors plus a ground floor that will function as an office building with analysis using a Structure Analysis Program (SAP 2000 v.19) combined with steel regulations on SNI 1729: 2015. Based on the results of SAP analysis 2000 v.19 produces a column structure using WF Steel 400x400x30x50 with the beam 1 using the profile of Steel WF 350x300x14x23 and for the beam 2 using the profile of Steel WF 200x200x9x14. For anchor and baseplate using anchor M-25 with a length of 400 mm, with baseplate thickness of 25 mm and for bolts using M-25 bolts with a total of 16 bolts.